From protection of sacrificial self to critical turning points and growth: Redeployed nurses’ experiences on the frontline during the COVID-19 pandemic - Sinéad Creedon; Anna Trace (PLoS ONE, 2025)
The mental health and wellbeing of nurses has been a concern, long before the arrival of the COVID-19 pandemic. Working on the frontline under such challenging circumstances, for extended periods of time, has resulted in negative psychological responses. The current study aims to examine redeployed nurses’ resilience in acute hospitals in Ireland, during a period of adversity (pandemic). The impact on their personal and professional identity, and their perception of meaningful supports and coping will be explored. An interpretative phenomenological analysis was carried out to gain insight into how nurses adapted to the changing work environment during the pandemic. Online semi-structured interviews were carried out with six experienced female nurses, who were redeployed to the frontline from their own roles. Three experiential themes representing the nurses’ journey were generated: Protection of Sacrificial Self; The Fortifying Effect of Us, and Critical Turning Points & Growth. Nurses made significant sacrifices and had to find ways to detach to cope. They revitalized themselves by creating a sense of ‘us’ to help them face a harsh climate against others, which enabled critical turning points and growth. This study has strongly highlighted the emotional effects on nurses due to feeling isolated, undervalued, and excluded during redeployment to the frontline. It has also featured how well redeployed nurses coped while faced with an existential crisis. It has given voice to all nurses who faced this pandemic, despite exposure to a risk of burnout and threats to their mental health and wellbeing. This study has further enriched our understanding of personal growth and trauma in adverse work conditions by including an exploration of what sacrificial commitment adds to our understanding of physical and moral courage. Future provision of supports for nurses must be ongoing both during and after crisis events.